Comorbidity Assessment in Skin Cancer Patients: A Pilot Study Comparing Medical Interview with a Patient-Reported Questionnaire - Erica H. Lee; Rajiv I. Nijhawan; Kishwer S. Nehal; Stephen W. Dusza; Amanda Levine; Amanda Hill; Christopher A. Barker (Journal of Skin Cancer)
Background. Comorbidities are conditions that occur simultaneously but independently of another disorder. Among skin cancer patients, comorbidities are common and may influence management. Objective. We compared comorbidity assessment by traditional medical interview (MI) and by standardized patient-reported questionnaire based on the Adult Comorbidity Evaluation-27 (ACE-27). Methods. Between September 2011 and October 2013, skin cancer patients underwent prospective comorbidity assessment by a Mohs surgeon (MI) and a radiation oncologist (using a standardized patient-reported questionnaire based on the ACE-27, the PRACE-27). Comorbidities were identified and graded according to the ACE-27 and compared for agreement. Results. Forty-four patients were evaluated. MI and PRACE-27 identified comorbidities in 79.5% and 88.6% (p=0.12) of patients, respectively. Among 27 comorbid ailments, the MI identified 9.9% as being present, while the PRACE-27 identified 12.5%. When there were discordant observations, PRACE-27 was more likely than MI to identify the comorbidity (OR=5.4, 95% CI = 2.4–14.4, p<0.001). Overall comorbidity scores were moderate or severe in 43.2% (MI) versus 59.1% (PRACE-27) (p=0.016). Limitations. Small sample size from a single institution. Conclusion. Comorbidities are common in skin cancer patients, and a standardized questionnaire may better identify and grade them. More accurate comorbidity assessments may help guide skin cancer management.